Assessment of maternity care services among pregnant women in a coastal area in central Kerala, India - Soman, Sajith Kumar; Areekal, Binu; Varghese, Rosin George; Murali, Asha Joan (International Journal Of Community Medicine And Public Health, 2017)
Background: Maternal care services are intended to take care about the pregnant during the antenatal, intra natal and post natal periods so as to reduce maternity related health problems. The current study tries to assess maternity care services among pregnant women in a coastal area in central Kerala, India. Methods: The setting was Mararikkulam south panchayat and the study was cross sectional in nature. The minimum sample size of the study was calculated to be 213. A house to house survey was conducted in all the 23 wards to find out those who had a live or still birth in the last one year (2014-2015) who were our study subjects. The maternity care services were assessed using multiple indicators. In statistical analysis, data was entered in Microsoft excel and was analysed using SPSS 16.0 version Results: As per the current study the number of pregnancies registered early i.e. within 12 weeks was 72.2%. Only 68% had all the antenatal check-ups while 26.1% had less than 4 antenatal check-ups and 5.9% had no regular antenatal check-ups. 67.7% of the mothers had taken iron and folic acid for the prescribed period of pregnancy. Ultrasound examination was done at least once during the pregnancy in 63.3% of cases and not done in 36.7%. For tetanus prophylaxis 84.5% had appropriate course of TT vaccination. 73.5% of the mothers were well aware of the danger signs of pregnancy and 21.2% were partially aware and 5.3% were unaware of the danger signs.